Lady Amelia's scandalous secret - Shepherd, Eva (Harlequin historicals., 2023)
When debutante Lady Amelia Lambourne is presented to self-made entrepreneur Leo Devenish at a Society dinner, he has no idea she has a scandalous secret; she runs a magazine for women! He might be charismatic and handsome, but she knows he's keen to take over her magazine. So she permits him to court her--but only to keep her enemy as close as possible...